A systematic review examining the effectiveness of blending technology with team-based learning. (October 2016) - River, Jo; Currie, Jane; Crawford, Tonia; Betihavas, Vasiliki; Randall, Sue
Abstract: Background: Technological advancements are rapidly changing nursing education in higher education settings. Nursing academics are enthusiastically blending technology with active learning approaches such as Team Based Learning (TBL). While the educational outcomes of TBL are well documented, the value of blending technology with TBL (blended-TBL) remains unclear. This paper presents a systematic review examining the effectiveness of blended-TBL in higher education health disciplines. Objectives: This paper aimed to identify how technology has been incorporated into TBL in higher education health disciplines. It also sought to evaluate the educational outcomes of blended-TBL in terms of student learning and preference. Method: A review of TBL research in Medline, CINAHL, ERIC and Embase databases was undertaken including the search terms, team based learning, nursing, health science, medical, pharmaceutical, allied health education and allied health education. Papers were appraised using the Critical Appraisal Skills Program (CASP). Results: The final review included 9 papers involving 2094 student participants. A variety of technologies were blended with TBL including interactive eLearning and social media. Conclusion: There is limited evidence that blended-TBL improved student learning outcomes or student preference. Enthusiasm to blend technology with TBL may not be as well founded as initially thought. However, few studies explicitly examined the value of incorporating technology into TBL. There is a clear need for research that can discern the impact of technology into TBL on student preference and learning outcomes, with a particular focus on barriers to student participation with online learning components. Highlights: Student attitudes are positive towards the implementation of TBL in higher education. There is limited evidence that blending technology with TBL improves student learning outcomes. Overall student attitudes are negative towards the blending of technology with TBL. There is some evidence that student preference for blended-TBL may improve over time.